Competitiveness of beekeeping industry in Malaysia - Ismail, Mohd Mansor (Universiti Putra Malaysia Press, 2014)
The Malaysian beekeeping industry is an important and integral component of the agricultural sector, providing additional income to farmers and indirectly producing food for the population through pollination services. The contribution of the beekeeping industry to regional development in Malaysia depends to considerable extent on its competitive potential in terms of producing and marketing of bee products and by-products efficiently. Beekeeping plays a major role in socio-economic development and environmental conservation in Malaysia. It is a source of health food (e.g. honey, royal jelly, pollen and propolis), raw materials for various industries (e.g. beeswax candles and lubricants) and medicine (honey, propolis, beeswax and bee venom). It is an important income generating activity especially for communities leaving close to the tropical forests and forest reserves (Acacia spp), and coastal areas where gelam and mangroves are found. Beekeeping also plays a major role in enhancing biodiversity and increasing crop production through pollination. In terms of production, most of the natural honey produced in Malaysia is from Sarawak, Sabah, Johor and Melaka and the bees are from the species of Apis cerana (local bees) and Apis mellifera (imported bees). The annual yield from local bees is about 5-9 kg per colony and the imported bees is expected to produce up to 15 kg per colony. Usually marketing involved a system of direct selling because producers try to avoid adulteration since the local honeys from different bee species and nectar sources are sold at premium prices. The balance of trade for natural honey is always negative until 2008. In 2009 the country recorded its first trade surplus in natural honey. The declining exports and the increasing imports from the period 2000 to 2009 reflects increased domestic consumption of natural honey and possibly for re-export, thus, reflecting insufficient local supply to meet the domestic demand for natural honey. The imports of natural honey amounted to RM13.86 million in 2000 and the value had increased in 2009 to RM32.85 million. This implies that, with increasing total trade and the domestic demand, the production of natural honey can contribute to the improvement of the country food trade balance. However, the analysis of comparative advantage and competitiveness at the production and at the frontier levels is scarce. Although Malaysia is not a major exporter of bee products and by-products, this potential industry could contribute significantly to the total export earnings of the country, and hence, improve the country’s food trade deficit. The study utilized primary data from consumers and producers survey and secondary data from FAO statistics and Global Trade Information System. Since the local production cannot cope with the domestic demand for natural honey, it is the aim of this study to investigate the current production issues, marketing problems, and trade performance of the Malaysian beekeeping industry. The issues and challenges of the beekeeping industry are discussed using a Porter Diamond approach and the probable solutions considered to improve the competitiveness position of the industry.